PEMAHAMAN SILA-SILA PANCASILA DALAM MENGIMPLEMENTASIKAN KEHIDUPAN SEHARI-HARI DI KALANGAN SISWA SEKOLAH DASAR - SHELA ANDRI MAULIDDINA; Dinie Anggraeni Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to identify and analyze the Understanding of the Five Principles of Pancasila in Implementing Daily Life among Elementary School Students, especially those related to the values of the principles of Pancasila. This research used a descriptive qualitative method. This method analyzed information or material obtained from various references such as books, journals, and articles. Based on the results of the analysis, it is concluded that each principle of Pancasila is valuable and had functions in the everyday life among elementary school students; they are also interrelated with one another. Whether it's in the life of fellow humans or fellow creators. Humans cannot live alone because humans have interdependence with each other; it is the legal connection applied by the Indonesian government. Pancasila is a view of life or a symbol of the Indonesian nation. Pancasila is the thought of our life, Pancasila is a meaningful guideline and elementary school students must practice it in everyday life. Pancasila is related to the points that must be applied to elementary school students both in the environment, at home, at school.